Budaya Tabu pada Masyarakat Banyumas - Muhammad Faisal Bisma; Rosdiana Puspita Sari; Gigih Ariastuti Purwandari (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This research aims to know taboo cultures in Banyumas Society. Banyumas is one of the regencies in Central Java. The method that is used is qualitative descriptive. This method does not use numeric or mathematical and statistical count in the interpretation of data. The source of the data are from the interview and literature review about taboo culture in Banyumas and surrounding. The result of the research shows that there are six kinds of taboo cultures in Banyumas based on Wardhaugh’s classification, which are sex, death, excretion, bodily function, religious matters and politics. Religious matter is the most taboos that appear in Banyumas culture. The society believe that those taboo cultures are prohibited to do because those who violate that taboo will get unexpected sanction and punishment.